Family(ies) in studies about school coexistence in Chile: a systematic review - Jonathan Andrades-Moya; Elsa María Castrillón Correa; Eugenio O. Pérez-Álvarez; Andrew Philominraj (Journal of Education and Learning (EduLearn), 2020)
Studies on school coexistence generally focus on the interaction between those who make up an educational institution. Many studies, in Chile, focus on students, teachers, and the management team, leaving aside other educational agents as educational assistants. The present study seeks to: a) Know whether research on school coexistence carried out in Chile considers family(ies) as an educational actor; b) Identify how their participation is assumed in processes related to school coexistence reported by research in this field. A systematic review was carried out for this purpose, selecting 27 articles processed through the prism flowchart. There is little consideration of the family(ies) as an active educational agent in studies of school coexistence in Chile. This makes the family(ies) invisible, reducing their responsibility and possibilities of participation as active agents in the constructive and interactive processes of school coexistence and the educational process of the new generations in their charge. These results show the need to strengthen this field of study and to promote the recognition of the family(ies) as active educational agents in the construction of school coexistence.